Two broken pieces make a whole: adductor canal block - Nagtilak, Harshada Hanamant; Deshmukh, Vidhya; Gupta, Ankit; Mehta, Hemant (International Journal of Research in Medical Sciences, 2021)
Total knee arthroplasty (TKA) is expounded to intense postoperative pain with a desire for early ambulation and reduce postoperative complications. Adductor canal blockade (ACB) blocks primarily the pain sensation while preserving the quadriceps strength facilitating early rehabilitation after knee surgery. ACB has been gaining popularity over femoral nerve block (FNB), continuous epidural analgesia (CEA), and psoas compartment block (PCB). Studies show that use of ultrasound alone reduced the possibilities of vascular and multiple skin punctures. Though there's emerging evidence proving the efficacy of ACB, there's limited literature on safe use of continuous ACB catheters. We report 2 cases of catheter fracture with USG guided ACB employed in TKA.